PENGARUH STRES KERJA TERHADAP KEPUASAN KERJA KARYAWAN DI PT. SKY INVESTMENT INDONESIA. - Meiliana Enok, Frischilia; Wijono, Sutarto (Universitas Sahid Surakarta, 2023)
The purpose of this study was to determine the effect of job stress on employee job satisfaction at PT SKY Investment Indonesia. This research uses a quantitative approach. The population in this study were 180 employees of PT SKY Investment Indonesia, the sample technique used was random sampling of 40 production employees. The data collection technique used a job stress scale and a job satisfaction scale in the form of a quisoner, data analysis used a simple linear regression technique. The results showed that there was no effect of work stress on job satisfaction of PT SKY Investment Indonesia employees.